Consumer Preferences in Traditional Markets Regarding Purchase Interest in Local Oranges and Imported Oranges in Surakarta - Muharom Zuhri Abdulloh; Sugiharti Mulya Handayani; Agustono Agustono (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2026)
Oranges are one of the horticultural commodities that play an important role in fulfilling community nutritional needs and have high economic value. The increase of orange consumption in Indonesia has not always been accompanied by stable local orange production, causing imported oranges to emerge as a complementary alternative supply in traditional markets. This condition has led to substitution between local and imported oranges, which affects consumer preferences. This study aims to analyze traditional market consumer preferences for the attributes of local and imported oranges in Surakarta City and to identify the attributes most considered in determining purchase intention. This research used a quantitative descriptive method with survey techniques, used primary and secondary data, with purposive sampling through observation and interviews using questionnaires. This Study used 100 respondents divided among three traditional markets in Surakarta. The traditional markets used as research sites were Pasar Gede Hardjonagoro, Pasar Legi, and Pasar Nusukan. Data were analyzed using the chi-square test and the Fishbein multi-attribute model. Consumer preferences for local oranges include thin fruit peel, sweet–slightly sour taste, medium fruit size, and juicy water content. Consumer preferences for imported oranges include thick fruit peel, sweet taste, medium fruit size, and very juicy water content. Fruit taste is the most considered attribute by consumers in determining purchase intention for both local and imported oranges.